How to Bring ESG Into the Quarterly Earnings Call - Tomlinson, Brian; Tomlinson, Brian; Whelan, Tensie; Eckerle, Kevin (MIT Sloan Management Review, 2021)
Quarterly earnings calls present an opportunity for businesses to share how their long-term financial performance is tied to environmental, social, and governance (ESG) issues. They can overcome obstacles to discussing ESG in these calls by laying the groundwork for interest in ESG, adapting the call schedule, explaining and reporting on the return on ESG investment, developing cross-functional collaborations, and staging the call as theater.